A Critical Realist Perspective of Education. - Shipway, Brad (New Studies in Critical Realism and Education, 2010)
Explores the capability of critical realism to throw light on educational theory. This book investigates the convergence and divergence between two forms of critical realism. It outlines the key characteristics that are necessary for a theological position to claim the term 'critical realist'.